Association between ecological risks and ecosystem services in an urban agglomeration in arid China - Huang, Shiwen; Song, Wei; Gao, He; Cao, Congjie; Li, Junfang; Liu, Bo; Yu, Hao; Li, Shuchang; Wei, Xi; Sheng, Shuangqing (Frontiers in Environmental Science, 2023)
Rapid urbanization leads to changes in ecosystem services and may exacerbate ecological risks. Clarifying the relationship between these two factors in a specific context is essential to explore the integrated management model and achieve sustainable regional development. However, previous studies mainly lack an integrated analysis, fail to clearly explain the mechanism of ecosystem change, and can neither support landscape ecological security construction nor spatial planning and management. This study, using the urban agglomeration on the northern slope of the Tianshan Mountains (UANSTM) as an example, applied multi-source data from 2010 to 2020, investigated the changes and relationships between ecological risks and ecosystem services, and proposes an assessment framework. The total ecosystem services (TES) of the studied agglomeration showed a decreasing trend, with an overall loss of 0.43%. Corresponding to the decrease of ecosystem services, the ecological risk was higher in the south and north of the UANSTM and lower in the northwestern, central, and eastern regions. The proportion of ecological high-risk areas was expanding. The key to the relationship between ecological risks and ecosystem services is the change in hydrological conditions. Therefore, we suggest that the UANSRM actively transforms the development and use mode of water resources and coordinates their allocation, with the aim to reduce regional ecological risks and optimize the pattern of ecosystem services.